2021
DOI: 10.3390/ijms222413429
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on HOX Genes as Potential Biomarkers in Colorectal Cancer: An Emerging Role of HOXB9

Abstract: Emerging evidence shows that Homeobox (HOX) genes are important in carcinogenesis, and their dysregulation has been linked with metastatic potential and poor prognosis. This review (PROSPERO-CRD42020190953) aims to systematically investigate the role of HOX genes as biomarkers in CRC and the impact of their modulation on tumour growth and progression. The MEDLINE, EMBASE, Web of Science and Cochrane databases were searched for eligible studies exploring two research questions: (a) the clinicopathological and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Indeed, studies by Hoshino et al and Huang et al have reported a positive association between high HOXB9 protein levels and lymph node invasion, presence of distant metastases, and poor differentiation in patients with CRC [11,12]. Additionally, in our systematic review, we found by conducting a post hoc meta-analysis that high HOXB9 expression levels were associated with a significantly increased risk for metastases (OR 4.14, 95% CI: 1.64-10.43, p = 0.003) [10]. In our CRLM patient group, although we did not find a significant association with the adverse CRLM characteristics, we noticed that high HOXB9 levels were positively correlated with the presence of metastatic disease in the regional lymph nodes at the time of the primary cancer resection, indicating that HOXB9 may promote CRC progression and affect survival.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Indeed, studies by Hoshino et al and Huang et al have reported a positive association between high HOXB9 protein levels and lymph node invasion, presence of distant metastases, and poor differentiation in patients with CRC [11,12]. Additionally, in our systematic review, we found by conducting a post hoc meta-analysis that high HOXB9 expression levels were associated with a significantly increased risk for metastases (OR 4.14, 95% CI: 1.64-10.43, p = 0.003) [10]. In our CRLM patient group, although we did not find a significant association with the adverse CRLM characteristics, we noticed that high HOXB9 levels were positively correlated with the presence of metastatic disease in the regional lymph nodes at the time of the primary cancer resection, indicating that HOXB9 may promote CRC progression and affect survival.…”
Section: Discussionsupporting
confidence: 50%
“…Likewise, the experimental observations also differed between studies with regard to the role of HOXB9 in CRC progression. Our study, Huang et al [11] and Hoshino et al [12] reported a potential tumour promoting role of HOXB9 whereas Zhan et al [13] observed a potential tumour suppressive function of HOXB9 in CRC [10]. Variability in the selection of downstream functional assays could be one reason for the contradictory findings.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations